Pelatihan Pengembangan Kompetensi Guru Dalam Pembuatan Video Pembelajaran Berbasis Youtube - Desyani, Teti; Ardiansyah, Hendri; Machfud, Syaeful (LOSARI DIGITAL, 2026)
The rapid development of information technology requires teachers to utilize digital media in the learning process; however, the use of instructional videos remains limited and tends to be conventional. This community service program aims to improve teachers’ competencies in designing and producing YouTube-based learning videos as an innovative instructional medium. The implementation method employed a participatory approach consisting of needs analysis, conceptual training, video production and editing practice, mentoring, and evaluation stages. The participants were teachers of SMP Negeri 16 Jakarta who were actively involved throughout the training process. The results indicate a significant improvement in teachers’ competencies, where understanding of instructional video concepts increased from 35% to 85%, video editing skills improved from 20% to 78%, and the ability to upload and publish content on YouTube increased from 25% to 90%. In addition, the program produced 18 instructional videos, established 12 active YouTube channels, and enabled 15 teachers to independently create learning videos. Furthermore, the program encouraged behavioral changes toward more interactive, creative, and student-centered learning practices. This community service activity contributes to supporting sustainable digital learning transformation within the school environment.